2015
DOI: 10.1186/s13568-014-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Exoproteome analysis of Clostridium cellulovorans in natural soft-biomass degradation

Abstract: Clostridium cellulovorans is an anaerobic, cellulolytic bacterium, capable of effectively degrading various types of soft biomass. Its excellent capacity for degradation results from optimization of the composition of the protein complex (cellulosome) and production of non-cellulosomal proteins according to the type of substrates. In this study, we performed a quantitative proteome analysis to determine changes in the extracellular proteins produced by C. cellulovorans for degradation of several types of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…First, we focused on profiles of metabolism-related proteins, such as enzymes involved in substrate degradation and metabolism, and other characteristic metabolic pathway. C. cellulovorans is known to change production of carbohydrate-related enzymes secreted into media from exoproteome analyses (Esaka et al 2015 ; Matsui et al 2013 ) and alternation of production of different metabolic pathways depending on which substrates are available in culture is also predicted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we focused on profiles of metabolism-related proteins, such as enzymes involved in substrate degradation and metabolism, and other characteristic metabolic pathway. C. cellulovorans is known to change production of carbohydrate-related enzymes secreted into media from exoproteome analyses (Esaka et al 2015 ; Matsui et al 2013 ) and alternation of production of different metabolic pathways depending on which substrates are available in culture is also predicted.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly annotated genes are part of mannan metabolic pathways in other bacteria (Senoura et al 2011 ), and we observed increased levels of proteins in this pathway (Clocel_3198, 3205) in the presence of galactomannan. However, Clocel_3197, which is known to play an important role in the mannan metabolic pathway (Esaka et al 2015 ), was only identified in our qualitative proteome analysis (Additional file 2 : Table S2). This protein has been also detected with “exoproteome” analysis (Esaka et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude solution was centrifuged at 12,000 × g for 10 min at 4°C, and the supernatant was obtained. After reduction, alkylation, and digestion by trypsin of each supernatant, the tryptic digests were subjected to nano liquid chromatography (LC)-mass spectrometry (MS)/MS analysis (Esaka et al, 2015).…”
Section: Sample Preparation For Proteome Analysismentioning
confidence: 99%
“…The xynA and xynB genes have been cloned and confirmed to have xylanase activity (Kosugi et al, 2002;Han et al, 2004). Additionally, proteome analysis verified that C. cellulovorans expresses XynA and XynB proteins (Morisaka et al, 2012;Matsui et al, 2013;Esaka et al, 2015;Aburaya et al, 2015). We believe that these two xylanases play an important role in the hydrolysis of the xylan contained in lignocellulose.…”
Section: Introductionmentioning
confidence: 99%